2022
DOI: 10.3390/plants11243505
|View full text |Cite
|
Sign up to set email alerts
|

Saponin Biosynthesis in Pulses

Abstract: Pulses are a group of leguminous crops that are harvested solely for their dry seeds. As the demand for plant-based proteins grows, pulses are becoming important food crops worldwide. In addition to being a rich source of nutrients, pulses also contain saponins that are traditionally considered anti-nutrients, and impart bitterness and astringency. Saponins are plant secondary metabolites with great structural and functional diversity. Given their diverse functional properties and biological activities, both u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Multiple researchers have reported that plants containing high amounts of saponins can boost the immune system by affecting the immune organ maturation and increasing the antibody levels in the body, providing better defense against cecal coccidiosis ( 164 , 179 182 ). Plants containing saponins also function as astringents, i.e., they reduce surface tension inside the body and help nutrients enter the cells ( 183 , 184 ). Due to these activities, multiple saponin-containing plants have been used to control coccidiosis ( 101 , 105 , 119 , 185 – 190 ).…”
Section: Methodsmentioning
confidence: 99%
“…Multiple researchers have reported that plants containing high amounts of saponins can boost the immune system by affecting the immune organ maturation and increasing the antibody levels in the body, providing better defense against cecal coccidiosis ( 164 , 179 182 ). Plants containing saponins also function as astringents, i.e., they reduce surface tension inside the body and help nutrients enter the cells ( 183 , 184 ). Due to these activities, multiple saponin-containing plants have been used to control coccidiosis ( 101 , 105 , 119 , 185 – 190 ).…”
Section: Methodsmentioning
confidence: 99%
“…According to the study of Arabidopsis thaliana in medium, the rise in sucrose increased the substrate for MEP action by activity-induced SnRK1 (sucrose non-fermenting 1-related protein kinase 1) phosphorylation and the light-induced metabolism by light-induced IPP. It has been reported to increase MEP-derived terpenoids by increasing dimethylallyl pyprophosphate (DMAPP) production [24]. It can be said that biosynthetic patterns can vary depending on environmental conditions.…”
Section: Network and Interpretation Of Phytochemicals In Ofc Extractmentioning
confidence: 99%
“…In pea, β‐amyrin C‐24 hydroxylase ( CYP93E8 ) has been the only experimentally proven enzyme for the oxygenation of saponins (Moses et al, 2014). However, in soybean, the biochemical identities of β‐amyrin C‐22 hydroxylase ( CYP72A61 ), galactose‐, rhamnose‐, and DDMP‐transferase ( UGT73P2 , UGT91H4 , and UGT73K5 , respectively) have been fully elucidated (Yu et al, 2022, and references therein). The enzyme for the transfer of glucuronic acid to the C‐3 hydroxyl position has been a mystery for decades, but a cellulose synthase superfamily‐derived glycosyl transferase ( CSyGT ) was recently identified as a catalyst for this reaction (Chung et al, 2020).…”
Section: Introductionmentioning
confidence: 99%